Accelerating Early Access to Immunotherapies for Advanced Urothelial Carcinoma. (27th November 2017) - Ning, Yang‐Min; Maher, V. Ellen; Beaver, Julia A.; Goldberg, Kirsten B.; Blumenthal, Gideon M.; Pazdur, Richard
Abstract : Within one year, five immunotherapies have been approved for the treatment of patients with locally advanced or metastatic urothelial cancer. The availability of these immunotherapies brings challenges to all stakeholders in the field. Additional research is needed to identify biomarkers that are predictive of individual patient response to different immunotherapies.